Motion Control of 5-Degree of Freedom Humanoid Robot Arm System Using Fuzzy Logic Algorithm - Ike Bayusari; Darma Sandi; Rahmawati Rahmawati; Suci Dwijayanti; Bhakti Yudho Suprapto (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2024)
Humanoid robots are the evidence of the rapid advancement of technology in robotics. One of their applications is replacing humans in certain tasks, such as moving goods. For this type of activity, humanoid robots need arms; however, their arm system is not effective enough because of the material used. Thus, this study proposes the use of filament as the material of frames in robot arms. A 5-degree of freedom (DoF) robot arm system was implemented, and the motor worked as the driving force. The movement of this robotic arm was based on proximity and camera sensor readings. Then, the movement control used fuzzy logic with the Sugeno method. During experimental testing, the humanoid robot arm could grip and move objects from one place to another at varying times according to the object type. The length of time obtained depends on the reading of the proximity sensor on the gripper. In another experiment, the humanoid robot arm could shake hands with humans in real time within 36 sec. In conclusion, the results verified the effectiveness of the proposed fuzzy logic controller with the Sugeno method.